Use of stroke rate, distance per stroke and velocity relationships during training for competitive swimming - Craig, A. B.; Boomer, W. L.; Gibbons, J. F. (Swimming III. Proceedings of the Third International Symposium of Biomechanics in Swimming, University of Alberta, Edmonton, Canada, 1979)
The locomotion of all animals can be characterized by the intermittant application of force that moves the body. Applying this principle to swimming, velocity (V) is the product of stroke rate ( S) and the distance moved through water with each complete stroke cycle (d/S). These relationships of S, d/S, and V were described for competitive swimmers with varying skills, and the results were compared with those observed during the 1976 U.S. Olympic Trials (Craig and Pendergast, 1978). In general, increased V was achieved by increasing Sand decreasing d/S (Figure 1). The front crawl swimmers who had the greatest maximal V also had the longest d/S at S of 20-25 S/min. For the males there was a direct relationship between the maximal V and the proportional decrease in dl S. The relationships of S and V during the freestyle events at the Olympic Trials are shown in Figure 2. The faster V of the 100-m versus the 200-m race for men was accounted for by an increase in S from 46 to 54 S/min and a decrease in d/S from 2.27 to 2.03 m/S. Similar changes for both the men and women were noted in the 100- and 200-m backstroke and breaststroke events. In effect, these points represent a short section of a stroke rate-velocity curve (S- V) for very skilled swimmers. The S used by the men in both the 400- and 1,500-m freestyle distances was 44 S/min, and the slower V of the 1,500-m race was accounted for by a shorter d!S. Theoretically, each race could have been swum at a slower S and a longer d/S. However, to achieve the same V at a slower S, a greater force for each stroke would be needed, and greater local muscle fatigue would result. Such considerations might also account for the observation that the 100-m butterfly races for both men and women were swum with a longer d/S and a faster S than was used in the 200-m events. Freestyle races for women were quite different from those for men. In the 400-, 200-, and 100-m events the increase in V was accounted for entirely by the increase in S, from 52 to SS to 58 S/ min, respectively, and the d/S values were not different (1.76 m/S). The S used in the 800-m race was the same as in the 400-m race, but d/S decreased to 1. 73 m/S. These differences between men and women who swam the front crawl may be related in some way to the energetics of swimming (di Prampero et al., 1974; Holmer, 1975). These observations have implications for swimming coaches. We wish to indicate how relationships of S, d/S, and V can be useful in practice. As much as possible, programs for competitive swimmers should be based on experimental evidence related to the sport rather than speculation and extrapolation from generalities.